Viscosity of Aluminium Oxide (Al2O3) Nanoparticle Dispersed in Ethylene Glycol - N. A., Usri; Azmi, W. H.; R., Mamat; Khamisah, Abdul Hamid (Trans Tech Publications Inc., 2014)
Researchers in applied thermal engineering found that nanofluid have potential as a heat transfer fluid with high level of enhancement in heat transfer process compared to conventional coolants. This study present investigation on viscosity for nanoparticles Aluminium Oxide (Al2O3) dispersed in ethylene glycol prepared using two step method. Viscosity measurement is conducted using Brookfield LVDV-III Viscometer at temperature ranging from 30 °C to 80 °C. Nanofluid is prepared using Al2O3 in 13 nm size at volume concentration ranging from 0.5 % to 2.0 %. The result indicates that viscosity for Al2O3 nanofluid is 75.2 % higher than based fluid at 1.5 % volume concentration and temperature of 30 °C. It was observed that viscosity is inversely proportional with the increment of nanofluid volume concentration and temperature.